The genus Dryadella (Orchidaceae, Pleurothallidinae) in Brazil - Imig, Daniela Cristina [UNESP] (2024)
The present work is a taxonomic revision of the Dryadella species of Brazil. Dryadella comprises 61 species, distributed in humid or seasonally humid forests, from Mexico to southern Brazil, most in the Atlantic Rainforest and the Andean forests. We provide morphological descriptions, taxonomic discussions, illustrations, an identification key, new synonyms, new occurrences and distribution maps for all taxa. Fourteen species are recognised for Brazil, of these D. zebrina recorded also for Bolivia and Peru, D. aviceps in Paraguay, D. lilliputiana in Bolivia, D. gnoma in Ecuador, Peru, Colombia, Panama, and Costa Rica and recorded for the first time in Brazil. The others are endemic to the country and, with the exception of D. gnoma, which occurs in the Amazon and D. ana-paulae, which occurs in the Cerrado, the other species are restricted to the Atlantic Rainforest. We propose the synonymisation of D. osmariniana and D. cardosoi in D. gnoma, D. espirito-santensis, D. gomes-ferreirae and D. litoralis in D. aviceps, D. vasquezii in D. ana-paulae and D. xaveriana in D. toscanoi. Nine lectotypes are designed.